Association between Vegetarian Diet Consumption and Academic Performance, Sleep Quality, and Health-Related Quality of Life among Female Undergraduate College Students - Rana F. Obeidat; Aisha S. Almadhaani; Amal K. Almemari; Ghareibah M. Alyammahi; Hamdah E. Alabdouli; Maryam M. Alhmoudi (Journal of Nutrition and Metabolism)
Purpose. This cross-sectional survey study aimed to examine the association between vegetarian diet consumption and sleep quality, academic performance, and health-related quality of life among female undergraduate college students. Method. A sample of 158 undergraduate female college students was recruited using a convenience sampling approach. Data collection utilized reliable and validated English-language instruments including the Vegetarian Quality of Life Questionnaire (VEGQOL), Pittsburgh Sleep Quality Index (PSQI), and health-related quality of life scale (HRQoL). The data were analyzed using one-way analysis of variance (ANOVA) and appropriate descriptive statistics. Results. Vegetarians exhibited a significantly lower BMI compared to nonvegetarians (F (1, 156) = [6.09], p=0.015). Those strictly adhering to a vegan diet (48.79 ± 9.41) had the lowest vegetarian quality of life among all participants following various forms of a vegetarian diet (F (3, 68) = [2.78], p=0.04). The majority of female college students reported good to excellent general health (91.7%), with 53.2% perceiving their sleep quality as fairly good. However, the mean PSQI global score of 8.04 (±3.35) indicated poor sleep quality. No significant association was found between diet type (vegetarian vs. nonvegetarian) and academic performance (cGPA) (χ2 (4, N = 158) = 2.92, p=0.57). There was no significant relationship between diet types and academic performance, HRQoL, and sleep quality. Conclusion. Despite a significant association between vegetarian diet and lower BMI, surprisingly, no substantial relationships were identified between diet type and academic performance, HRQoL, and sleep quality. These findings contribute to the ongoing discourse on the potential impacts of a vegetarian diet on various facets of female college students’ well-being and highlight the need for further exploration in this field.